Application of Electronic Land Certificates in The Indonesian Land System - Deska Suryani BR M, Stevani; Neltje Saly, Jeane (Pusat Publikasi Nusantara, 2024)
As the era develops, which is supported by technological developments into the digital era, everything becomes easier and more practical. Likewise in Indonesia, which has begun to follow the development of the digital era. In order to realize modernization in connection with the digital era, services in the land sector in Indonesia have also begun to apply land services based on electronics to produce legal products in the form of electronic documents. The Electronic Land Certificate itself was launched in the Regulation of the Head of the National Land Agency regarding Electronic Certificates which was signed by the Minister of Agrarian Affairs Sofyan Djalil on January 12, 2021. The purpose of this study is to provide knowledge and understanding of how to apply electronic certificates to the public. Through normative juridical methods and tracing document studies from laws and regulations to scientific journals, the research results will be used to analyze this study. The results of the study show that the application of electronic land certificates is something that cannot be prevented due to the increasingly advanced developments in today's digital era.